Penggunaan Metode Simulasi Guna Menentukan Jumlah Tenaga Kerja Kesehatan di Instalasi Rawat Darurat RSUD Dr. Saiful Anwar Malang - Murti Astuti, Dian Heriani (Jurnal Teknik Industri, 2000)
The amount of hospital in a row with increasingly of the society level, 50 level hospital is demanded to diectly fix up and increase the servility system. The servility system very significant in competent to satisfy the patient. One of parameter to eveluate good or bad a servicing system is a patient wait time. This research take a sample at this emergency treatment Instalation RSUD Dr. Saiful Anwar Malang. Where the patient that come have to be handled correctly and quickly, because the patient that enter to the Emergency Treatment lnstallation in IRD must wait too long time will cause physical defect even death. There for this research is intended to analyze patient servicing system, determine the sum the health power, and the sum of maximal patient that can be handled y emergency treatment Installation, so got the wait time that is fit with patient aspiration level.